(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
Providing the necessary resources to the business is a key issue in its performance. The financial analysis methods enable to evaluate the effectiveness of the company’s policy in the sphere of assets management. The enterprise’s assets as an object of financial analysis are considered. The issues of preparation of financial information on the assets for the purposes of analysis are investigated. Carrying out such procedures is traditionally stipulated by a desire to provide information in a simplified, more illustrative form. However, the authors put an emphasis on another, more important reason for the financial statements transformation – it is the need to ensure the reliability of information which has to reflect the real value of assets. The criteria underlying the construction of an analytical balance are reviewed. The basic methodological approaches to conducting horizontal and vertical analyses of assets and its individual components are described. The purpose and methodology of conducting the assets analysis are designated. The criteria for assessing the dynamics and structure of assets are defined. Some «positive» and «negative» characteristics of individual groups of assets, which are to be considered when analyzing the active operations, are also identified.